Restructuring of Undergraduate Information Technology Curriculum in Fulfillment of SKKNI Industry 4.0 with an Independent Learning Campus Approach - Batmetan, Johan Reimon; Rumagit, Selvie Serly; Mamuaja, Marlin Penina; Tiwow, Gilly Marlya; Naharia, Orbanus; Sumual, Shelty D.M. (JR Education, 2023)
Information technology has played an important role in the business and industrial environment. The suitability of the competence of graduates of information technology graduates and competency standards in the industry is a problem that is quite complicated to explore. The purpose of this study was to analyze the suitability of the undergraduate-level information technology curriculum with the competency map required by the industry which is always developing rapidly in the industrial era 4.0. This study also tries to recommend an information technology curriculum restructuring model with an independent campus learning approach. The method used in this study is a qualitative method with a traditional literature review approach that specifically analyzes documents in depth to gain new knowledge. The results of this study indicate that there is a large gap between the education process at the undergraduate level in the competencies students acquire and the occupations provided by industry which results in many undergraduate graduates not being absorbed by industry. The results of this study also show that the independent approach to independent campus learning is also not enough to bridge this gap because several stages do not go well. This study concludes that a comprehensive restructuring of the undergraduate curriculum is needed to obtain a curriculum that is good and adaptive to change.